Emotions and learning motivation of high school students in biotechnology learning under the Merdeka Curriculum - Rina Karwatisari; Adi Rahmat; Sariwulan Diana (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
Research on students' emotions and motivation in biotechnology learning is very important as key input for considering the development of appropriate learning strategies. This study aims to determine the emotions and motivations of high school students in biotechnology learning. Using a quantitative descriptive method, data on students' emotions and motivations collected from 69 respondents are presented in representative graphs. The student respondents were selected using cluster random sampling. The emotion questionnaire instrument used amounted to 20 items based on indicators from PANAS-GEN. Meanwhile, the motivation questionnaire instrument used amounted to 15 items based on indicators from SALES. Descriptive statistical analysis shows that students' emotions toward biotechnology learning are dominated by positive emotions with an average score of 60 points. The positive emotions among students are more prevalent in the moderate category, accounting for 44% of students. The highest positive emotional values are found in students' enthusiasm for biotechnology learning. Meanwhile, negative emotions among students are dominated by the moderate category, accounting for 34%. The highest negative emotion scores were found in the aspect of fear in biotechnology learning. On the other hand, the results of students' motivation in biotechnology learning mostly fall into the low and moderate categories. The highest motivation indicator value was found in the ‘learning goal orientation’ indicator. Of the three, positive and negative emotions toward motivation showed a significant relationship with moderate levels of relationship quality. These findings provide empirical evidence that positive emotions and motivation play a significant role in supporting the development of 21st-century skills in learning.Abstrak. Penelitian mengenai emosi dan motivasi siswa dalam pembelajaran bioteknologi sangat penting sebagai masukan utama untuk mempertimbangkan pengembangan strategi belajar yang tepat. Penelitian ini bertujuan untuk mengetahui emosi dan motivasi siswa SMA dalam pembelajaran bioteknologi. Dengan menggunakan metode deskriptf kuantitatif, data hasil emosi dan motivasi siswa yang diambil dari 69 responden disajikan dalam bentuk grafik yang representatif. Responden siswa dipilih dengan teknik cluster random sampling. Instrumen kuesioner emosi yang digunakan terdiri dari 20 item berdasarkan indikator dari PANAS-GEN. Sementara itu, instrumen kuesioner motivasi yang digunakan terdiri dari 15 item berdasarkan indikator dari SALES. Analisis dengan statistik deskriptif menunjukkan bahwa emosi siswa terhadap pembelajaran bioteknologi didominasi oleh emosi positif dengan rata-rata nilai 60 poin. Emosi positif siswa lebih banyak pada kategori sedang sebanyak 44% siswa. Nilai emosi positif tertinggi ada pada aspek antusias siswa dalam pembelajaran bioteknologi. Kemudian, emosi negatif siswa didominasi kategori sedang sebanyak 34% dan kategori tinggi sebanyak 30%. Nilai emosi negatif tertinggi ada pada aspek takut dalam pembelajaran bioteknologi Disisi lain, hasil motivasi siswa dalam pembelajaran bioteknologi paling banyak termasuk dalam kategori rendah dan sedang. Nilai indikator motivasi siswa tertinggi ada pada indikator ‘learning goal orientation’. Dari ketiganya, antara emosi positif dan negatif terhadap motivasi menunjukkan adanya hubungan yang signifikan dengan taraf hubungan yang sedang. Temuan ini menjadi dasar empiris bahwa emosi positif dan motivasi berperan signifikan dalam mendukung pengembangan keterampilan abad 21 dalam pembelajaran.